Perubahan Pola Perilaku Pengguna Layanan Paylater yang Terintegrasi dengan e-Commerce dalam Perspektif Behavioural Design - Laila Quthratun Nada; Riyadi, Slamet (Jurnal Sosioteknologi, 2024)
The cashless trend in using e-wallets has replaced conventional payment methods and become a daily necessity. This frugal digital transformation has significant implications for society and presents new challenges. It addresses impulsive purchasing habits and the emergence of the online lending trend. Each design decision has a lasting impact on the development of digital financial services in e-commerce, influencing changes in user behavior patterns and leading to a new lifestyle transformation in shopping. This study examines behavioral design through online ethnography, surveys, and interviews to assess how design interventions influence decisions to use Paylater services. This paper broadens the investigation into the application of behavioral design in the development process, which aids in pinpointing the most effective stages, thereby enhancing the design and reducing the risk associated with user interaction. Researchers have found that alterations in interactions with objects can also shape and create new behaviors that challenge systems, environments, and lifestyles. Research findings conduct the design strategy gap for integrating user needs and adjustments in the stage of behavior change in navigating Paylater services integrated with e-commerce platforms.